Strategi Pemerintah Desa dalam Meningkatkan Pendapatan Asli Desa (PADes) Desa Tanjung Harapan Kecamatan Singkep Kebupaten Lingga 2023 - Muhammad Rafi Akbar Nasuha; Afrizal Afrizal; Kustiawan Kustiawan (Universitas Maritim AMNI Semarang, 2024)
Tanjung Harapan Village has various potential natural and human resources that can be optimized to increase PAD. However, Tanjung Harapan Village faces various challenges in optimizing the potential of natural and human resources in the village. The problems faced include limited resources, low capacity of village officials. Therefore, this research aims to analyze the strategies implemented by the Tanjung Harapan Village government in an effort to increase PADes. This research aims to analyze the strategies implemented by the Tanjung Harapan Village government, Singkep District, Lingga Regency, in an effort to increase Village Original Income (PADes). Highlighting the importance of PADes as a source of financing for village development and improving community welfare. This research uses a descriptive method with a qualitative approach. Data collection was carried out through in-depth interview techniques with village officials and community leaders, participatory observation of village resource management activities, as well as documentation studies related to village financial policies and reports. The data obtained was analyzed using qualitative analysis techniques which included data reduction, data presentation, as well as drawing conclusions and verification to ensure the validity of the findings. The results reveal that the Tanjung Harapan Village government has implemented several main strategies to improve PADes, namely optimizing natural resources through more effective management, increasing the capacity and competency of village officials through training and continuous education.